PKM. PENDAMPINGAN ANAK MELINIAL DALAM MELESTARIKAN SENI PEWAYANGAN BALI SEBAGAI WARISAN BUDAYA LELUHUR DI BANJAR PADANG, DESA KEROBOKAN, KECAMATAN KUTA UTARA KABUPATEN BADUNG, BALI - I Ketut Muada; I Nyoman Astawan; I Made Indra Sanjaya (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
In addition to its religious function, the Balinese shadow puppet performance art also functions as an educational medium. In this regard, shadow puppet performances can be seen as an informal educational process that has great significance in understanding attitudes, mental, ethical and logical values. In order to preserve Balinese wayang kulit, the role of millennial youth is very important and complex, namely as heir artists (dalang) who preserve wayang art. In general, shadow puppet shows today are still the favorite of the Balinese people, but in several villages the existence of wayang is almost extinct because millennial young people as heirs do not want to learn wayang for reasons of being busy so that one day the art of wayang could be lost. The case is in Banjar Padang, Kerobokan Village, North Kuta District, three regenerating families of shadow puppet masters do not want to learn wayang so they need assistance. The wayang art companion will provide an understanding of the preservation, function and meaning of Balinese wayang, so that service to the community, especially in the world of wayang art, can be realized.